The COVID-19 crisis from the perspective of global trade flows: A review - Cajas-Guijarro, John (2022)
This paper discusses the potential implications of the relationship between international trade flows and the COVID-19 crisis. The discussion departs from a review of economic literature focused on multiple aspects of the coronavirus-trade interaction with special attention on the role of international trade networks and global value chains. Also, the paper proposes that the economic consolidation of China through its participation in international trade may cause a relevant structural change in global capitalism and a higher economic dependency of the capitalist periphery.